Influence of activators on spent coffee grounds as biosorbent for chromium - Yustira Ayuni; Arif Hafifuddin; Zahedi Zahedi; Razi Fachrur (Chemical Industry and Chemical Engineering Quarterly)
Global production of Cr(VI) can reach 44 million metric tons annually, of which 49% is released into the environment. Developments in the industry are to blame for this. There are numerous ways to defend against the damaging impact that heavy metals have on the environment. The presence of Cr(VI) causes environmental problems because it can endanger the physical and ecosystem balance of aquatic fauna in river flows. Exposure to Cr(VI) causes health problems such as liver, lung, and kidney damage. Adsorption is a straightforward, affordable, and user-friendly technique. The adsorbent utilized is derived from biomass waste, specifically spent coffee ground (SCG), but its potential as an adsorbent still needs to be developed. The purpose of this work was to examine the impact of activators on activated SCG and its capacity to adsorb Cr(VI) compounds. Nitric and bromide acid were used to activate 25 g of SCG for 1, 2, and 3 hours. Adsorbent-to-activator ratios were 1:4, 1:5, and 1:6. Cr(VI) solution was started at a concentration of 100 mg/L, and the adsorption process was stirred at 300 rpm. In the adsorption process, a ratio of 1:6 was best, along with an HNO3 solution (pH 4) as the best activator, a contact time of 120 minutes, and an initial Cr(VI) concentration of 20 mg/L. OH is the major functional group of both adsorbents.